How Body-Centering Improves the Effects of Core Stability Training on the Motor Skills in Adolescent Female Volleyball Players - Arianna Fogliata; Fioretta Silvestri; Lorenzo Marcelli; Maria Chiara Gallotta; Davide Curzi (Journal of Functional Morphology and Kinesiology, 2025)
Background: During growth, the reduction in motor control makes core stability training essential, especially in sports involving dynamic jumps. Given the limited training time of adolescent athletes, finding strategies to maximize the effects of core stability training is crucial. This study analyzed the effects of incorporating body-centering techniques (a method that involves conscious modulation of intra-abdominal pressure to enhance postural stability during motor gestures) into a core stability training protocol on balance, trunk control, and lower limb explosive strength in adolescent volleyball players. Methods: Forty-four female volleyball athletes (15.6 ± 1.4 years of age) were randomly divided into three experimental groups: G1 = body-centering + core stability training; G2 = core stability training; and G3 = standard conditioning session. The athletes performed 30 min of differentiated intervention training twice a week for 8 weeks. Balance ability (Berg Balance Scale—BBS and Stork balance stand test—SBST), trunk control (Trunk Control test—TCT), and lower limb explosive strength (broad jump—BJ, squat jump—SJ, and drop jump—DJ) were assessed at the beginning (T0) and the end (T1) of the intervention period, and 12 weeks later (T2). Results: Data showed a significant improvement of BBS, SBST, DJ (p < 0.01), and TCT (p < 0.05) in G1 and G2 at T1 compared to T0, which persisted until T2 except for DJ in both groups. SJ improved only in G1 at T1 compared to T0 (p = 0.016). G1 showed a higher rate of improvement in SBST (T1: +18.2%; T2: +16.8%) and in DJ (T1: +3%) compared to G2 (SBST T1: +7.6%, T2: +5.2%; DJ: +2.5%). In addition, only G1 showed a significant improvement rate in BBS score (+2.2%) compared to G3 (+0.4%) at T1. Conclusions: These results suggested that core training improves balance, trunk control, and explosive strength in young volleyball athletes with and without body-centering. However, integrating body-centering into core exercises leads to better balance and jumping power than core stability training alone.